FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN NON KEUANGAN DI BEI - Olivia, Sandra; Susanti, Merry (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This aims to obtain empirical evidence regarding the effect of earnings per share, managerial ownership, firm age and debt to equity ratio on firm value in non-financial companies listed in the Indonesia Stock Exchange for the 2017-2019 period. The sample was obtained based on the purposive sampling method and the final data used in this study found 135 non-financial companies. The data processing technique used multiple regression analysis assisted by Econometric Views 9. The results showed that the variables of earnings per share, managerial ownership and debt to equity ratio had no significant effect on firm value. Meanwhile, the firm age variable has a significant negative effect on firm value. The implication of this research is the need for the role of company management in paying attention to the age of a company as a strategy to be able to maintain and even increase the value of the company in the future.